The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.ijresmar.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Generating global brand equity through corporate social responsibility to key stakeholders

Abstract: a b s t r a c t Keywords:Global brands Brand equity Corporate social responsibility StakeholdersIn this paper, we argue that corporate social responsibility (CSR) to various stakeholders (customers, shareholders, employees, suppliers, and community) has a positive effect on global brand equity (BE). In addition, policies aimed at satisfying community interests help reinforce the credibility of social responsibility policies with other stakeholders. We test these theoretical contentions by using panel data comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
214
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(232 citation statements)
references
References 66 publications
13
214
1
4
Order By: Relevance
“…Our results revealed no statistically significant relationship between CSR and brand value, thus reinforcing the conclusions of Torres et al (2012). Therefore, for our selected companies that implemented CSR activities could became difficult to determine whether CSR influences brand value or vice-versa.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results revealed no statistically significant relationship between CSR and brand value, thus reinforcing the conclusions of Torres et al (2012). Therefore, for our selected companies that implemented CSR activities could became difficult to determine whether CSR influences brand value or vice-versa.…”
Section: Discussionsupporting
confidence: 78%
“…These benefits had been considered in many studies important key factors towards development of different CSR concepts. Researchers have tried to examine in their studies the effect of CSR on brand and failed or found inconclusive results (Torres et al, 2012). We argue that once a company integrates CSR activities in its core business strategies and is taken seriously, not as a fashion, CSR becomes a part of the company's brand, therefore increasing it.…”
mentioning
confidence: 87%
“…A possible explanation of this outcome is that ESG initiatives and performance may differ in their visibility, allowing firms to offset strategically. In this regard, Torres et al [61] showed that local social responsibility policies in communities generate brand value and foster the positive effect of corporate social responsibility toward other stakeholders, particularly customers. In line with this argument, those firms that concentrate their efforts to be leaders on those extra-financial categories that have the greatest visibility may increase the effectiveness of ESG practices to stakeholders and credibility to the firm, obtaining better economic performance than those firms that intends to stand equal or above their peers in all the extra-financial categories.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…This is valid also when talking about markets and customers (Torres et al 2012;Vallaster et al 2012;Macleod 2001;Mohr et al 2001). When a firm acts in the abovementioned fields, the definition of the sum of the concerns affecting its strategy is Corporate Social Responsibility (CSR), which has been actively implemented by companies over the last few decades (Candelo et al 2014).…”
Section: From Corporate Social Responsibility To the Territory Value mentioning
confidence: 99%